Features of environments for cage fish farming in the Astrakhan Region on example of the Khurdun River - O. V. Pyatikopova; I. N. Bedritskaya; S. A. Diakova; D. A. Popov; O. G. Tarasova; E. V. Makarova; E. V. Minakova; O. V. Zhatkina; R. D. Kashin (Известия ТИНРО, 2024)
Cage aquaculture is a relatively low-cost and quite effective method of fish farming, particularly important for the Astrakhan Region in recent times. Sturgeon species are grown in the farms there mainly. The most favorable conditions for cage aquaculture are provided in flowing water of both natural and anthropogenic nature. Features of environments for cage fish farming are considered for several operating fish farms at the Khurdun River that is rather demanded for these enterprises due to accessibility to roads, proximity of settlements and so suitability for the farm servicing and selling the products. However, the river is rather impacted to anthropogenic activity, including pollutions from the fish farming itself. Standard methods of hydrology, chemistry and biology were used. The fish farms at Khurdun River were differed in their production capacity and the volume of aquaculture production, though the depth of the cage lines installation was sufficient for the fish growing everywhere. The flow velocity was rather slow and decreased at cages of the most farms relative to the background value. Dissolved oxygen content in water was quite high, but great vertical differences were observed in summer, with supersaturation at the water surface and oxygen consumption for oxidation of organics at the river bottom. The value of chemical oxygen consumption exceeded the norm both at the surface and at the bottom and increased downstream. By taxonomic composition of bioindicator benthic organisms, the studied water body was classified to categories from “clean” to “very dirty”. Some deterioration of environmental quality downstream from the cage lines was detected relative to background values. Sanitary and microbiological tests of water revealed an exceeding of the total microbial count at 22 o С relative to this one at 37 o С in all seasons, that is a sign of water self-purification worsening. Faecal pollution of the river water was found and confirmed by a presence of Enterococcus faecalis in abnormal concentration, in particular in summer-autumn low-water season. In general, environmental conditions in some sites of the Khurdun River can be considered as tense in the summer-fall season by a number of parameters. Deterioration of environmental regime in conditions of rising temperature and slowing flow in the summer-fall low-water season should be accounted for adjustment of planting density and feeding of farmed fish.